THE INFLUENCE OF GROUP INVESTIGATION LEARNING STRATEGIES AND LEARNING INDEPENDENCE ON THE RESULTS OF LEARNING MATERIALS HUDUD STUDENTS OF CLASS XI MADRASAH ALYAH NEGERI 1 MEDAN - Nahar, Syamsu; Saputra, Edi; JP, Daisy (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
This study aims to determine and describe: (1) the effect of implementing learning strategies on the learning outcomes of students in class XI Madrasah Aliyah Negeri 1 Medan, (2) the effect of independent learning on learning outcomes of hudud material for class XI students of Madrasah Aliyah Negeri 1 Medan, and (3) the  interaction between learning strategies and independent learning on learning outcomes  of hudud material for class XI students of Madrasah Aliyah Negeri 1 Medan.  This research is a quantitative research. The population of this research was all students of class XI Madrasah Aliyah Negeri 1 Medan which consisted of 19 classes. Based on the Cluster Random Sampling technique, one class is a Group Investigation  learning class and one expository learning class. This research instrument is a test and questionnaire used to obtain data on learning outcomes and to determine student independence. The normality test of learning outcomes data is the Liliefors test and the homogeneity test is the Fisher test and the Bartlett test. The data analysis technique was two-way ANOVA at significant α = 0.05 followed by the Scheffe test. The results of the study indicate: (1) there is an effect of the application of learning strategies on learning outcomes of hudud material. In this case the average learning outcomes hudud material of class XI Madrasah Aliyah Negeri 1 Medan taught with the Group Investigation learning strategy ( = 28) was higher than the average hudud material learning outcomes of class XI Madrasah Aliyah Negeri 1 Medan students who were taught with an expository learning strategy ( = 26.92) with Fcount = 53.61 > Ftable = 3.968, (2) there is an effect of independent learning on learning outcomes hudud material. In this case the average learning outcomes of hudud material for class XI Madrasah Aliyah Negeri 1 Medan students with high learning independence ( = 29.93) were higher than the average learning outcomes of students in class XI Madrasah  Aliyah Negeri 1 Medan with independent learning. low ( = 25.93) with Fcount = 8.02 > Ftable = 3.968, and (3) there is an interaction between learning strategies and learning independence, where for students with high learning independence it is more appropriate to use Group Investigation learning strategies, while students with independence Low learning is more appropriate to use expository learning strategies with Fcount = 14.46 > Ftable 3,968.